Blast pressure analysis due to confined explosion-after effects. (December 2020) - Choubey, Bishwajeet; Dutta, Sekhar Chandra; Prakhya, Ganga Kasi V.; Mandal, Parthasarathi; Kumar Tanwar, Rajesh
Highlights: The confined explosion from a stored high explosive by a full scale blast is studied. The experimental results are obtained through a sensor based instrumentation. A comparative study of full scale field trial and Numerical analysis is presented. The effect is reduced by providing layered sand-air-sand and air-sand-air barriers. Abstract: The paper aims to analyse the effect of confined explosion of high-explosive materials in storage compartment. The present investigation proposes an improved structural configuration of the storage compartments for limiting the damage. An experiment was conducted in which a TNT charge had been detonated at the centre of a full-scale compartment constructed by following the Indian standards and the effect of the same was studied. Numerical simulation of the problems was obtained using a well-established software to supplement the experimental results for further understanding. The pressures developed at various locations (as obtained from Computation) were compared with the experimental data. The study also presents the development and validation of a non-propagating type sandwiched partition wall combinations so that it can reduce the severity of the damage. The effect of alternate materials and geometric changes are also studied through numerical models which increased the confidence in predictions. The study, thus, proposes alternate configurations to limit the damage due to the internal blast. Analytical study based on models calibrated with that of experiments gives reliability in the investigation even for few particular types of configuration of internal walls.